2016
DOI: 10.1016/j.juro.2016.03.075
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Anteriorly Located Prostate Cancer and the Usefulness of Multiparametric Magnetic Resonance Imaging for Diagnosis

Abstract: Anterior prostate cancer had pathological features and favorable oncologic outcomes comparable to those of posterior prostate cancer but also more frequent Gleason score upgrading. Magnetic resonance imaging had moderate diagnostic performance for detecting lesions in the anterior prostate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 26 publications
2
24
4
Order By: Relevance
“…With regard to clinical and pathologic features of csPCa developed after nMRI in patients who underwent RP, we found, as previously reported, that prostatitis and benign prostatic hyperplasia can mask PCa [22] and that small tumors near the anterior horn can be missed at mpMRI [27], possibly indicating that the reader experience is extremely important to avoid false negative, as also shown by the PROMIS trial, which was based on quality control of mpMRI and systematic training of radiologists [12].…”
Section: Discussionsupporting
confidence: 77%
“…With regard to clinical and pathologic features of csPCa developed after nMRI in patients who underwent RP, we found, as previously reported, that prostatitis and benign prostatic hyperplasia can mask PCa [22] and that small tumors near the anterior horn can be missed at mpMRI [27], possibly indicating that the reader experience is extremely important to avoid false negative, as also shown by the PROMIS trial, which was based on quality control of mpMRI and systematic training of radiologists [12].…”
Section: Discussionsupporting
confidence: 77%
“…Especially, lesions in the apex or anterior of the prostate are difficult to find. In these cases, MRI is useful for identifying occult anterior lesion cancers [26]. However, the purpose of the follow-up MRI in our study was not to detect upgrading or upstaging but to make a decision about early biopsy or to make target biopsy easier.…”
Section: Discussionmentioning
confidence: 96%
“…African Americans are more likely to have anterior tumors, which are more likely to have Gleason upgrading ( Sundi et al, 2014 ). However, Kim et al recently reported that anterior tumors have similar extracapsular extension, positive margins, and lymph node invasion compared with posterior tumors and that anterior tumors have significantly higher rates of 5-year biochemical-free recurrence survival ( Kim et al, 2016 ). They hypothesized that a barrier formed by the anterior horn of the peripheral zone or anterior fibromuscular stroma and fewer lymphatics and blood vessels could be the reason for such results.…”
Section: Discussionmentioning
confidence: 99%